Pelaksanaan Teknik Problem Solving untuk Meningkatkan Kecerdasan Emosional Siswa SMP Negeri 4 Padang Panjang - Fadila, Dia Sri; Afrinaldi, Afrinaldi (ALSYS, 2023)
This research departs from the phenomenon that there are students who have low emotional intelligence, in which students often utter harsh words and mock each other between one student and another so that it can be said that students have not been able to control or regulate their emotions in learning and socializing and students also not being able to build good relationships with friends around him and Shiva also doesn't know how to improve his emotional intelligence.The goal to be achieved in this study is to find out whether there is a significant difference or improvement between before and after being given problem solving techniques to improve the emotional intelligence of SMPN 4 Padang Panjang students. This research is a pre-experimental study using the One Group Pretest and Posttest Design model. The population is grade 8.2 students of SMPN 4 Padang Panjang, while the sample is 11 students who are indicated to have emotional intelligence problems based on the purposive sampling technique and the results of the pretest. The instrument that the authors use in data collection is the Likert scale. The data analysis technique used the Wilcoxon test, while the data analysis requirements used hypothesis testing with the help of SPSS version 25.The results of research that have been known from the results of the Z test (Wilcoxon) show that there is a difference between the pretest and posttest values. From the results of the Wilcoxon test calculation, a significant p-value of 0.003 was obtained. Based on the applicable regulations, it is known that the results of the Wilcoxon Sig test are p-value of 0.003 <α (α = 0.05), which means that Ha is accepted and Ho is rejected. From the results of the Wilcoxon test calculations, it can be concluded that students' emotional intelligence has increased after being given treatment using problem solving techniques.